Let f(x) and g(x) be two odd functions defined for all real values of x. Given that s(x)=f(x)+g(x), prove that s(x) is also an odd function.

We recall that a function f(x) is said to be an odd function when f(-x)=-f(x).

We are told that f(x) and g(x) are odd functions, so we know from the above definition that:

1. f(-x)=-f(x)

2. g(-x)=-g(x)

Solution

We want to show that s(x) is an odd function. In other words, we want to show that s(-x)=-s(x) (that it satisfies the above definition).

We are told that s(x)=f(x)+g(x), so substituting x for -x, we get that

s(-x)=f(-x)+g(-x)

=-f(x)-g(x) (using 1 and 2)

=-(f(x)+g(x))

=-s(x) as required!

We have now shown that s(-x)=-s(x) and thus we have proven that s(x) is indeed an odd function.

Answered by Keir H. Maths tutor

12532 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

The equation (t – 1)x^2 + 4x + (t – 5) = 0, where t is a constant has no real roots. Show that t satisfies t2–6t+1>0


How do I know which method of diffirentiation to use?


Express 4sin(x)+6cos(x) in terms of Rsin(x+a) where R and a are constants to be determined (a should be given in rad).


Find all possible values of θ for tan θ = 2 sin θ with the range 0◦ ≤ θ ≤ 360◦


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences